1995
DOI: 10.1103/physrevlett.74.2248
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Induced Damage in Dielectrics with Nanosecond to Subpicosecond Pulses

Abstract: This is a prepdnt of a paper intended for publication in a journal ozproceedinge. Since changer may be made before publication, thip preprint is made available with the understanding that it will not be cited ac reproduced without the permission of the author.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

32
675
5
11

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,294 publications
(723 citation statements)
references
References 11 publications
32
675
5
11
Order By: Relevance
“…The white emission is due to plasma formation. [10] It was also found that three areas, the white emission area, the gray area, and the nanoparticle-precipitated area were basically the same. If the diameter of the beam was kept the same (9 mm), the length of emission region was proportional to the light intensity, which increased from 1.2 10 14 to 4.0 10 15 W cm À2 .…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…The white emission is due to plasma formation. [10] It was also found that three areas, the white emission area, the gray area, and the nanoparticle-precipitated area were basically the same. If the diameter of the beam was kept the same (9 mm), the length of emission region was proportional to the light intensity, which increased from 1.2 10 14 to 4.0 10 15 W cm À2 .…”
mentioning
confidence: 85%
“…In general, the light intensity, in order of 10 14 -10 17 W cm À2 , is high enough to generate multiphoton ionization in the glass matrix. [10] Therefore, the active electrons and holes can be created in the glass through multiphoton ionization, Joule heating, and collisional ionization, [10] and form plasma, which yield white emission. Electrons are driven out of the valence states by multiphoton absorption of the incident photon.…”
mentioning
confidence: 99%
“…s [ 10 ps), where damage on the surface of a medium results from conventional heating and melting, the damage threshold scales as s 0.5 with pulse duration [21,22]. However, a deviation from this scaling has been observed for shorter pulses where damage results from plasma formation and ablation [17,22]. Although the ablation threshold in the short-pulse regime reduces with decreasing the pulse duration, this dependency is weaker than what is observed in the long-pulse regime.…”
Section: Introductionmentioning
confidence: 99%
“…Because the ionization of gases is mostly intensity driven and collective effects can be neglected, this ionization threshold is time independent on the subnanosecond scale. For dielectrics, a damage threshold following a square root law is reported and commonly accepted [9] at a level that is enhanced by the very small spot of the laser such that the band-gap collapse seen in largespot damage tests can be reduced [10] . For metals, a linear intensity dependency (constant fluence) is reported [11] for time scales from 10 ps to 1 ns.…”
Section: Requirement On the Ase Level In Petawatt Lasersmentioning
confidence: 99%